THE RELATIONSHIP BETWEEN WORD CHOICE AND QUESTION-ANSWERING ABILITY IN 2-3 YEARS OLD CHILDREN - Sabrina, Isabel Selmiola; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study examines the relationship between word choice and question-answering ability in children aged 2-3 years. The research involved five participants: two aged 2 years and three aged 3 years. Data were collected through observation and structured tasks, where children were asked five types of questions ("what," "who," "where," "why," and "how"). The results showed that 2-year-old children predominantly used basic nouns and verbs, while 3-year-olds demonstrated a more varied vocabulary, including adjectives and short phrases. In the question-answering task, 2-year-olds successfully answered 40% of "what" and "who" questions but struggled with "why" and "how" questions, achieving only 10% accuracy. In contrast, 3-year-olds answered 80% of "what," "who," and "where" questions accurately and performed moderately well with "why" (60%) and "how" (50%) questions. The findings indicate a positive correlation between vocabulary richness and the ability to answer questions. Children with broader vocabularies provided more accurate and contextually appropriate responses. This research highlights the importance of fostering language development during early childhood through interactive communication and exposure to diverse linguistic inputs.